Cziesław Miłosz about Reason in the Essay „PiesekPrzydrożny" ("Snoopy Doggy") - Kovtun, Asija (Respectus Philologicus, 2006)
The article considers the concept of reason in the essay "Piesekprzydrozny" (1998) written by the Nobel Prize winner Czesław Miłosz from the postructuralist perspective of deanthropologisation and decentration of the subject. The strategy used in the text analysis is deconstruction. Miłosz speaks about the destruction of the ego cogito in anthropology. He accepts the Nietzschean idea of the metaphoricity of the truth and the impossibility of perceiving the truth individually and by reason. Yet. be does not accept nihilism, attributing it to the sphere of mass culture.The author of the article comes to the following conclusion: Miłosz acknowledges that the man of the 20th century is dependent on Cartesian cogito. The thinker himself, however, in "Piesekprzydrożny" is closer to St. Augustine than to Descartes.